2017
DOI: 10.1016/j.livres.2017.11.003
|View full text |Cite|
|
Sign up to set email alerts
|

Decoding the role of extracellular vesicles in liver diseases

Abstract: Cell-to-cell communication is a fascinating process that is essential for maintaining tissue and whole-body homeostasis. Extracellular vesicles (EVs) are cell-derived membrane-bound nanoparticles that are a means of communication between cells. Accumulating evidence indicates that EVs can render either beneficial or harmful outcomes, depending on the specific cargos (e.g. proteins, lipids, RNAs) transferred between cells. EVs also have great value as diagnostic and prognostic markers of disease because they ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 103 publications
(146 reference statements)
0
30
0
1
Order By: Relevance
“…EVs have recently attracted considerable attention as an ideal miRNA delivery platform for therapeutic intervention of liver disorders, including hepatocellular carcinoma, due to their extremely low immunogenicity and toxicity profiles and to their ability to increase miRNAs stability in circulation [11,62]. In particular, transfer of miRNA by EVs isolated from mesenchymal cells have been shown to reduce liver fibrosis, promote hepatic regeneration after partial hepatectomy, modulate inflammatory response, and promote anti-tumor activity against hepatocellular carcinoma [4,63].…”
Section: Discussionmentioning
confidence: 99%
“…EVs have recently attracted considerable attention as an ideal miRNA delivery platform for therapeutic intervention of liver disorders, including hepatocellular carcinoma, due to their extremely low immunogenicity and toxicity profiles and to their ability to increase miRNAs stability in circulation [11,62]. In particular, transfer of miRNA by EVs isolated from mesenchymal cells have been shown to reduce liver fibrosis, promote hepatic regeneration after partial hepatectomy, modulate inflammatory response, and promote anti-tumor activity against hepatocellular carcinoma [4,63].…”
Section: Discussionmentioning
confidence: 99%
“…While NPs mainly comprises of liposomes, polymeric NPs, and organic or inorganic NPs, EVs are biologically formed membrane-derived vesicles that carry multiple bioactive molecules to regulate cellular responses [41,42]. NPs and EVs can both be selectively engineered for the delivery of several therapeutics including miRNA/siRNA, proteins/peptides, and small-molecule inhibitors to target hepatic macrophages for the treatment of liver diseases [43]. The major advantages of these delivery vehicles are improved stability, site-specific delivery, and thus increased pharmacokinetics of the encapsulated therapeutics [44].…”
Section: Therapeutic Targeting Of Hepatic Macrophagesmentioning
confidence: 99%
“…Gene expression is biologically regulated via RNA interference, wherein microRNAs (miRNAs) and small interfering RNAs (siRNAs) are fundamental. miRNAs and siRNAs are naturally occurring small non-coding RNA molecules composed of about 22 nucleotides that regulate gene expression via gene silencing at the posttranscriptional level [42,43]. New insights illustrate that miRNA and siRNA expression is specifically altered in nearly all liver diseases, suggesting the great involvement of dysregulation of these non-coding RNAs in liver pathology [45,46].…”
Section: Mirna/sirna-based Approachesmentioning
confidence: 99%
“…Studies using stem cell-derived EVs have demonstrated that exosomes, per se, are a novel therapeutic target for diseases [26,27]. Thus, MSC-derived EVs have been identified as an important therapeutic target for liver disease, to protect against acute tubular injury, and to reduce myocardial ischemia/perfusion damage [26,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…It has been described that there is an increase of circulating vesicles from liver origin after acute liver damage [33] and also in chronic liver conditions [34]. In addition, studies in relation to pathogenesis of different liver diseases have demonstrated implication of aberrant biogenesis of EVs [28].…”
Section: Introductionmentioning
confidence: 99%